Physician Talent Management in a VUCA (Volatility, Uncertainty, Complexity and Ambiguity) World: Gestão de Talento Médico num Mundo VUCA (Volatility, Uncertainty, Complexity and Ambiguity) - Prates, Ana Paula Mendes (Gazeta Médica, 2017)
In a world characterized by volatility, uncertainty, complexity and ambiguity, such as today, where we witness the exponential increase of scientific knowledge and a technological revolution - with strong impacts on the practice of medicine - allied to a situation of profound transformation of the health sector in Portugal, it will be necessary to rethink talent management strategies in general and physician talent management, in specific. In this article, we will present a perspective of the physician talent management, mainly based on the experience acquired in José de Mello Saúde, and through which we can contribute to enrich the debate on methodologies of attraction, development and motivation, with impact on satisfaction, quality of service delivery and recognition of patients and their families.